Effects of Active Learning and Adaptive Behavior on Personality of Football Players in China - Bole Sun (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
Football is the game of presence of mind with quality athleticism hence, the effects of psychological factors on the personality of football players cause vigorous results which ultimately affect the players’ actions and performances on the ground. It is the personality of the football players that plays a vital role in their consistent performances and building their careers in a highlighted way. According to the current study, active learning and adaptive behavior are the two major psychological factors which affect the confidence and personality of football players, particularly in China. To accomplish the objectives of the current study, a quantitative research approach was adopted. Hence, a survey was conducted to collect the primary data from the 450 football players who were the respondents of the current study, aimed to perform data analysis. The results revealed that an increase in active learning and adaptive behavior; causes an increase in the players’ confidence and personality. Hence, the current study helps the players and responsible authorities to make players’ personalities object-oriented.